Clinical and epidemiological aspects of Delta and Gamma SARS-CoV-2 variant of concern from the western Brazilian Amazon - Sgorlon, Gabriella (2022)
Fundação Oswaldo Cruz. Fiocruz Rondônia. Laboratório de Virologia Molecular, Porto Velho, RO, Brasil / Universidade Federal de Rondônia. Programa de Pós-Graduação em Biologia Experimental. Porto Velho, RO, Brasil.